King David's City at Khirbet Qeiyafa: Results of the Second Radiocarbon Dating Project. Issue 5 (2015) - Garfinkel, Yosef; Streit, Katharina; Ganor, Saar; Reimer, Paula J
Abstract : Seventeen samples of burnt olive pits discovered inside a jar in the destruction layer of the Iron Age city of Khirbet Qeiyafa were analyzed by accelerator mass spectrometry (AMS) radiocarbon dating. Of these, four were halved and sent to two different laboratories to minimize laboratory bias. The dating of these samples is 1000 BC. Khirbet Qeiyafa is currently the earliest known example of a fortified city in the Kingdom of Judah and contributes direct evidence to the heated debate on the biblical narrative relating to King David. Was he the real historical ruler of an urbanized state-level society in the early 10th century BC or was this level of social development reached only at the end of the 8th century BC? We can conclude that there were indeed fortified centers in the Davidic kingdom from the studies presented. In addition, the dating of Khirbet Qeiyafa has far-reaching implications for the entire Levant. The discovery of Cypriot pottery at the site connects the 14 C datings to Cyprus and the renewal of maritime trade between the island and the mainland in the Iron Age. A stone temple model from Khirbet Qeiyafa, decorated with triglyphs and a recessed doorframe, points to an early date for the development of this typical royal architecture of the Iron Age Levant.